2007
DOI: 10.1021/la702598g
|View full text |Cite
|
Sign up to set email alerts
|

Macro- to Nanoscale Wear Prevention via Molecular Adsorption

Abstract: As the size of mechanical systems shrinks from macro- to nanoscales, surface phenomena such as adhesion, friction, and wear become increasingly significant. This paper demonstrates the use of alcohol adsorption as a means of continuously replenishing the lubricating layer on the working device surfaces and elucidates the tribochemical reaction products formed in the sliding contact region. Friction and wear of native silicon oxide were studied over a wide range of length scales from macro- to nanoscales using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 29 publications
4
103
0
Order By: Relevance
“…Vapor phase lubrication of silicon oxide surfaces has been shown to be effective and reliable on the macro to the nano-scales [214,215]. Pentanol vapor lubrication completely prevented failure of MEMS devices; as Fig.…”
Section: Vapor Phase Lubrication Of Mems Devicesmentioning
confidence: 98%
See 3 more Smart Citations
“…Vapor phase lubrication of silicon oxide surfaces has been shown to be effective and reliable on the macro to the nano-scales [214,215]. Pentanol vapor lubrication completely prevented failure of MEMS devices; as Fig.…”
Section: Vapor Phase Lubrication Of Mems Devicesmentioning
confidence: 98%
“…14 shows, a MEMS device operated in dry conditions failed after less than 10,000 cycles (less than two min at a 100 Hz operation). In contrast, when the MEMS device was operated in the presence of pentanol vapor, the device ran for 11 days without failing or any sign of wear [215]. Under prolonged operation of the MEMS device at low partial pressure of pentanol vapor, a high molecular weight material was detected within the sliding area [215].…”
Section: Vapor Phase Lubrication Of Mems Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work, however, has demonstrated that gas-phase alcohols may provide a solution to the friction problem, in that when MEMS devices are exposed to low vapor pressures of short chain alcohols, devices with contacting, moving parts can run for billions of cycles without failure and with no visible wear [185]. While this appears to be a successful lubrication strategy, in order to move towards applications, a number of questions still need to be addressed.…”
Section: Introductionmentioning
confidence: 99%